Assurance on corporate governance reports in Spain: Towards an enhanced accountability or a new form of public relations? - Elies Seguí-Mas; Helena-María Bollas-Araya; Fernando Polo-Garrido (Administrative Sciences, 2018)
Financial scandals have highlighted the need for greater corporate transparency. Thus, corporate governance has emerged as an instrument for corporations to fulfil their social responsibility by offering more reliable information to their stakeholders. In this sense, the corporate governance report has become one of the leading mechanisms of business reporting to attend the growing need for reliable information by users. External and independent assurance of corporate governance reports is a tool to reduce potential risk derived from malpractices. However, within the Spanish context, there is a few number of listed companies who assure their corporate governance reports, and some of them have been shaken by corporate malpractices and financial scandals. This work tries to offer a critical appraisal of current corporate governance of assurance statements in Spain, developing a research strategy based on the case-study. Thus, by analysing assurance on corporate governance reports in three Spanish listed companies, we identify strengths and weaknesses of an unusual assurance process. Obviously, because of the recent scandals occurred in the analysed companies, we raise a particular concern about the potential managerial capture of this activity. Without real changes in governance mechanisms, the corporate governance assurance could amount to little more than a public relations activity.
Keywords: 350; corporate governance; assurance; quality reporting; case study; content analysis